2005
DOI: 10.1002/art.21005
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland epithelial cell exosomes: A source of autoantigenic ribonucleoproteins

Abstract: Objective. Exosomes are membrane vesicles of endosomal origin that are distinct from apoptotic bodies and are thought to represent an acellular mechanism for antigen transfer to classic antigen-presenting cells, as well as for direct antigen presentation with the capacity to induce immune response or tolerance. Nevertheless, it is not known whether exosomes are involved in the induction or regulation of immune responses against intracellular autoantigens that characterize autoimmune diseases. Exosomes have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
148
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(157 citation statements)
references
References 13 publications
2
148
0
4
Order By: Relevance
“…There are still many puzzles of ovarian cancer, including the relationship between the tumor and the host immune system, and the mechanisms of the development, invasion and metastasis of the tumor. Exosomes are a kind of microvesicles released by many types of cells such as tumor cell (1)(2)(3)(4), antigen presenting cells (APC) (5,6) and epithelial cells (7,8). Recent research revealed that exosomes purified from the ascites of patient with ovarian cancer contain some immunological-effect molecules (9).…”
Section: Introductionmentioning
confidence: 99%
“…There are still many puzzles of ovarian cancer, including the relationship between the tumor and the host immune system, and the mechanisms of the development, invasion and metastasis of the tumor. Exosomes are a kind of microvesicles released by many types of cells such as tumor cell (1)(2)(3)(4), antigen presenting cells (APC) (5,6) and epithelial cells (7,8). Recent research revealed that exosomes purified from the ascites of patient with ovarian cancer contain some immunological-effect molecules (9).…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37] In autoimmunity, it has also been suggested that exosomes play a role in the chronic inflammatory response and that the cellular origin of exosomes will differentially influence the immune response in autoimmune disease. 6,38,39 Our data are important because they emphasize that co-stimulatory molecules play a pivotal role in APC-mediated immune responses, particularly T-cell activation and proliferation. [40][41][42][43][44][45] In the study herein, we demonstrate the ability of autologous exosomes to be taken up by peripheral monocytes and DCs.…”
Section: Discussionmentioning
confidence: 81%
“…For example, exosomes derived from salivary gland epithelial cells contain the autoantigenic ribonucleoproteins in Sjögren's syndrome. 6 We have previously demonstrated that apoptotic bodies from biliary epithelial cells contained the PBC-specific mitochondrial autoantigens. 26 Hence, within the liver, it is likely that biliary epithelial cells may produce exosomes that are critical for the homeostasis of biliary function 52,53 and we further hypothesize that exosomes released by damaged bile duct cells may augment this process.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations